VISUALISASI DASHBOARD POWER BUSINESS INTELLIGENCE JUMLAH KERUGIAN KENDARAAN BERMOTOR DI JAWA TIMUR INDONESIA - Setyan, Ardath Prahara; Pratama, I Putu Agus Eka (Universitas Nusa Cendana, 2023)
East Java Province has a high number of motorized vehicle losses with various modes of crime. There needs to be a system that can process the data to assist the decision-making process for law enforcement officers in investigating the crime of motor vehicle theft and reducing the amount of loss. For this reason, in this research, data processing of motor vehicle theft was carried out using Business Intelligence (BI) and displayed on the Power BI dashboard. The research methodology used is literature study, interviews, data collection, implementation, evaluation, and documentation. The test results show the highest number of vehicle theft cases occurred in 2016 (1,635 cases) with the most modes using fake keys, and with the highest vehicle brand being Honda. The final result of the study shows that the presentation of data and information visually and interactively based on Power BI can help law enforcers to understand data, obtain information, and make decisions and policies to handle motorcycle theft cases.